(untitled) (Olhar de Professor, 2026)
This article investigates the linguistic beliefs of public school teachers in Buritizal (SP), focusing on their representations of language, linguistic variation, and teaching. Grounded in Educational Sociolinguistics (Bortoni-Ricardo, 2005) and studies on language attitudes (López Morales, 2004), the research adopts a qualitative methodology, using a test with 23 questions distributed across six thematic blocks. The analysis reveals a predominance of a normative view of language, with an emphasis on standard language and writing. However, signs of critical awareness emerge in topics such as linguistic identity and situational appropriateness. The responses indicate contradictions and tensions, highlighting the coexistence of traditional beliefs and the potential openness to more inclusive pedagogical practices. It is concluded that these beliefs are socially constructed, shaped by experiences and affective dimensions, and that continuing education plays a crucial role in reshaping these perspectives in favor of a more critical and diversity-sensitive approach to language teaching.